Comparing the silencing efficacy of dicer-independent and dependent shRNAs - Nhlabatsi, Neliswa (My University, 2015)
RNA interference (RNAi) is a highly conserved gene regulatory mechanism triggered by the presence of double-stranded RNAs and results in post-transcriptional and transcriptional gene silencing. RNAi has been demonstrated to have therapeutic potential to treat chronic viral infections including HIV-1. Due to the side effects of and eventual drug resistance to highly active antiretroviral therapy, a novel anti-HIV-1 therapy is required. The most suitable exogenous RNAi triggers to use in anti-HIV-1 RNAi-based therapy are expressed short hairpin RNAs (shRNAs). Despite being highly developed, shRNA systems still pose safety concerns. Highly expressed shRNAs are at risk of over-saturating the endogenous RNAi pathway, inducing an innate immune response or silencing off-target mRNA. The purpose of this study was to minimise shRNA-associated off-target effects and simultaneously maximise the potency and specificity of expressed shRNAs for potential therapeutic application. ShRNAs shorter than 19 base pairs are not recognised by the endonuclease Dicer, which is an important component of the RNAi pathway, but miR-451 is Dicer-independent. Smaller shRNAs that retain their potency would be easier to deliver into a disease model. For this study, 25mers and miR-451-mimicking 19mers were generated. The shRNA pairs exhibited significant knockdown of their respective targets in dual-luciferase assays. The 19mers are more specific gene silencers compared to the 25mers. A 19mer that is more potent than its 25mer counterpart was identified. None of the hairpins induced an innate immune response, caused cytotoxic effects or saturated the endogenous RNAi pathway. This study concludes that the 19mers were processed in a manner similar to miR-451 resulting in a single ~30 nt mature RNA product. We dubbed these miR-451-mimicking 19mers, guide shRNAs. The single RNA strand of mature guide shRNAs abolishes the risk sense strand-associated off-targeting thus improving shRNA specificity. These revolutionary guide shRNAs can be developed into highly potent activators of the RNAi pathway in a therapeutic setting.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2014.
Keywords: RNA-Induced Silencing Complex; RNA Interference; Antiviral Agents; Viruses